The multimedia development for learning writing - Lusia Oktri Wini; Atmazaki Atmazaki; Novia Juita (Fakultas Ilmu Pendidikan UNP)
This study aims to produce a multimedia learning narrative writing that is valid, practical, and effective for use by students. This type of research is a development study, which develops multimedia learning using the 4D development model that begins with the defining, designing, developing, and deploying stages. Instruments used in this study are questionnaires, observation sheets, and performance tests. Based on the results of data analysis and discussion can be concluded as follows. First, the validity of developed multimedia is quite valid that is the percentage 82.63%. Second, the developed multimedia practicability is very practical with the percentage of 81.75%. Third, the effectiveness of multimedia developed is effective with the percentage of 78,72% with 49 people from 51 students from two test schools reaching value above the national standardization. Thus, the multimedia that has been developed can be used as a teaching medium in learning Indonesian especially narrative writing materials.